Makna Frasa Kerjakan Keselamatanmu Dalam Filipi 2:12 Serta Implikasinya Bagi Orang Kristen - Suwandy Loardi; Ibrahim Ibrahim (Sekolah Tinggi Teologi Blessing Indonesia Makassar, 2023)
ABSTRACTThe purpose of this research is to find out the true meaning of the phrase work out your own salvation in Philippians 2:12. The method used in this paper uses descriptive qualitative research methods and biblical studies. The results of this research can be concluded that the command